A Novel Image Compression Algorithm Using Ridgelet Transformation with Modified EBCOT - Zhenghua Shu; Guodong Liu; Shengqian Wang; Chengzhi Deng; Lixin Gan; Lin Zhan (ISECS 2009 : Proceedings of the Second International Symposium on Electronic Commerce and Security : Nanchang, China, 22-24 May 2009, 2009)
JPEG2000 is the image compression standard which includes three core techniques: wavelet lifting scheme and EBCOT and MQ arithmetic coder. The EBCOT algorithm uses a Wavelet transform to generate the subband samples, which are quantized and coded. Normal Wavelet transforms fail to represent such functions effectively while Ridge functions are effective in representing functions that have discontinuities along straight lines. If the coefficients obtained from Ridgelet transform of the image with more discontinuities along straight lines have to be subject to quantization and coding process with EBCOT, the existing structure of the EBCOT should be modified to suit with the output of the Finite Ridgelet Transform (FRIT). In this paper, an effective image coding technique is proposed. The technique, which involves transforming the image into another domain with Ridgelet function and then quantizing and coding the coefficients with modified EBCOT, is similar to JPEG2000. A modified EBCOT algorithm for FRIT coefficients has been also proposed in this paper. Experimental results show the combination of modified EBCOT with FRIT which is used to code novel images such as images with straight lines and galaxy images significantly outperforms the combination of EBCOT with Wavelet Transform in novel image coding in terms of PSNR.